2012
DOI: 10.5194/bg-9-375-2012
|View full text |Cite
|
Sign up to set email alerts
|

Day and night warming have different effect on root lifespan

Abstract: Abstract.Roots are key components of C cycling in terrestrial ecosystems and play an important role in the regulation of response of terrestrial ecosystems to global climate warming, which is predicted to occur with greater warming magnitudes at night than during daytime across different regions on the Earth. However, there has been no detailed study to investigate the effect of asymmetrical warming on root dynamics at the level of terrestrial ecosystems. To understand the effects of day and night warming on r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…In general, warmer soil temperatures stimulate the rapid death of roots in warming treatment of 1.3 to 1.7 • C [35] and 5.0 • C [36]. However, in some cases, no change in FRM with 2.8 • C warmer treatment [37] or decreases in FRM with relatively weak warmer (0.3 to 1.4 • C) system [12,38] was observed. The contradictory results of previous studies might be explained by the water availability in each ecosystem [39].…”
Section: Effect Of Warmingmentioning
confidence: 99%
“…In general, warmer soil temperatures stimulate the rapid death of roots in warming treatment of 1.3 to 1.7 • C [35] and 5.0 • C [36]. However, in some cases, no change in FRM with 2.8 • C warmer treatment [37] or decreases in FRM with relatively weak warmer (0.3 to 1.4 • C) system [12,38] was observed. The contradictory results of previous studies might be explained by the water availability in each ecosystem [39].…”
Section: Effect Of Warmingmentioning
confidence: 99%
“…Different artificial warming scenarios, such as day, night, or diurnal warming, have shown differential effects on plant physiological traits and ecosystem productivity. For example, Bai et al (2012) observed that day warming can, but night warming cannot, prolong root lifespan. Also, Wan et al (2009) reported that day warming significantly decreased, while night warming increased, gross ecosystem productivity in the semiarid temperate steppe in northern China.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a cascade of studies have investigated plants responses to global warming (Lemmens et al, 2006;Vicca et al, 2007;Danby and Hik, 2007;Leppalammi et al, 2013;Zheng et al, 2013), such as structure, physiology and function of leaves (Jin et al, 2011;Zheng et al, 2013), root lifespan and physiology (Bai et al, 2012;Yin et al, 2014), plant phenology (K€ orner and Basler, 2010) and carbon gain (Gimeno et al, 2012) as well as net primary productivity (Hudson and Henry, 2009). It is reported that globally averaged maximum and minimum temperatures have both increased since 1950 (IPCC, 2013), which tends to affect carbon assimilation and consumptions in plants, because photosynthesis in most plants occurs during the daytime and is more sensitive to daily maximum temperature, whereas plants respiration occurs throughout the whole day (Atkin et al, 2013), and is therefore influenced by both daily maximum and minimum temperature (Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%